1998
DOI: 10.1042/bj3360611
|View full text |Cite
|
Sign up to set email alerts
|

Activation of phospholipase A2 in human neutrophils by polyunsaturated fatty acids and its role in stimulation of superoxide production

Abstract: Although polyunsaturated fatty acids (PUFA) have been shown to stimulate neutrophil responses such as the oxygen-dependent respiratory burst (superoxide production), the mechanisms involved still remain undefined. Here we investigate the effect of PUFA on the phospholipase A2 (PLA2)-signal transduction process in human neutrophils. Exogenous eicosatetraenoic acid [arachidonic acid; C20:4(n-6)] or docosahexaenoic acid [C22:6(n-3)] promoted the release of [3H]C20:4(n-6) from prelabelled neutrophils in a time- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 47 publications
(65 reference statements)
6
32
1
Order By: Relevance
“…This action of AA has been shown by different investigators in various cell types, particularly phagocytes, endothelial cells, 3T3 fibroblasts, and cancer cell lines (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Most published data indicate only a slight effect of AA on superoxide generation, probably because the superoxide assays normally used, such as the cytochrome c reduction system, can only determine extracellular superoxide.…”
Section: Discussionmentioning
confidence: 90%
“…This action of AA has been shown by different investigators in various cell types, particularly phagocytes, endothelial cells, 3T3 fibroblasts, and cancer cell lines (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Most published data indicate only a slight effect of AA on superoxide generation, probably because the superoxide assays normally used, such as the cytochrome c reduction system, can only determine extracellular superoxide.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, we have demonstrated that exogenous AA caused the activation of the cPLA 2 and secretory PLA 2 (28). This was accompanied by the release of [ 3 H]AA from prelabeled cells, and this could be inhibited by AACOCF3.…”
Section: Discussionmentioning
confidence: 93%
“…We have previously demonstrated that AA stimulates the activities of PKC, ERK1/ERK2, and phospholipase A 2 (27,28). To understand the mechanisms by which AA caused the up-regulation of TNFR, the chemical inhibitors, GF109203X, PD098059, and AACOCF3, were used to target PKC, ERK1/ERK2, and the cPLA 2 , respectively.…”
Section: The Role Of Pkc Erk1/erk2 and Cplamentioning
confidence: 99%
“…Moreover, a number of previous publications have reported that stimulation of phagocytic cells with AA, the product of PLA 2 activity, leads to the activation of NADPH oxidase, which then results in superoxide generation (31,43). The involvement of the two phospholipases, cPLA 2 and PLD 1 , in superoxide generation after treatment of human monocytes with WKYMVm was, therefore, further investigated.…”
Section: The Wkymvm-induced Stimulation Of Cpla 2 and Pld 1 Is Requirmentioning
confidence: 99%